The Effect of Leadership, School Climate, and Scientific Literacy on Teacher Creativity with the Role of Artificial Intelligence in Senior and Vocational High Schools in Samarinda - Rini Dwi Yuliani; Laili Komariyah; Azainil Azainil; Prita Indriawati; Descha Rahmadani; Rinda Rinda; Dwi Nopriyanto (FKIP - Universitas Riau, 2026)
This study examines the effects of principal leadership, school climate, and scientific literacy on teacher creativity, with artificial intelligence (AI) as an intervening variable. A quantitative survey was conducted involving 58 senior high school teachers in Samarinda. Data were collected through questionnaires and analyzed using SEM-PLS to evaluate the relationships among variables. The findings reveal that the model demonstrates good fit and predictive relevance. Principal leadership shows a positive but not statistically significant effect on teacher creativity, suggesting its role is supportive but not dominant. In contrast, school climate has a significant positive influence, indicating that a collaborative and supportive environment enhances creative teaching practices. Scientific literacy also significantly contributes to teacher creativity, emphasizing the importance of integrating scientific knowledge into instructional design. Furthermore, AI serves as a significant intervening variable, strengthening the relationship between the independent variables and teacher creativity. These results highlight the importance of integrating leadership, organizational climate, literacy, and technology in fostering teacher creativity. Practically, schools are encouraged to optimize leadership, build a conducive environment, and integrate AI to support innovative and effective learning.